THE COMPETENCE OF NURSE PROFESSIONAL STUDENTS ABOUT MODERN WOUND CARE WITH MOTIVATION FOR INDEPENDENT NURSING PRACTICE AT POLTEKKES KEMENKES YOGYAKARTA - Noamperani, Sapta Rahayu; Destiana, Destiana (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. One of the competencies of nursing students is wound care. The goal of moist wound healing treatment is to keep the wounds wet for the natural tissue growth as the wounds heal. For the community, the existence of independent nursing practices will make the community more able to obtain health services, especially in nursing services. People do not have to go to a hospital when there are health or nursing services around their residence. Method. This research is a descriptive study to identify student competence in wound care using a cross sectional design. Result and Analysis. From the research result, it is known that the r table for a sample size of 30 is 0.361. When the Cronbach's Alpha is bigger than 0.7 then it is reliable. The univariate tests were conducted to provide a descriptive picture. In numerical data, the analysis results were presented as mean ± SD. While the categorical data is presented in the form of frequency and percentage. The bivariate test used is Pearson correlation. When P < 0.05 then Ha is accepted (there is a significant relationship). Based on the results of the analysis, the value of P = 0.000 was obtained with r count = 0.589. Discussion. There is a significant positive relationship between competence and motivation. The level of motivation increases along with the competence.